Specific Properties of Some Medicinal Plants Information About - Abdukhalilova Madinakhon (International Journal on Orange Technologies, 2023)
The article contains information about some medicinal plants distributed in the territory of our country, which have an important place in the world of medicinal plants, and their effects on the human body.